2005
DOI: 10.1029/2004gl022224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GPS satellite antenna offsets on scale changes in global network solutions

Abstract: [1] In this paper, we demonstrate that biases in the GPS satellite antenna phase center offsets could lead to scale biases in global network solutions, which change along with the observed satellite constellation. To validate the IGS standard offset values, satellite-specific offsets are estimated from GPS data and the network solutions are re-adjusted with these estimates. Both the estimated offsets and the readjusted network scales confirmed that the IGS standard offsets are significantly biased and produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 9 publications
2
46
0
1
Order By: Relevance
“…This small relative drift is close to the estimated error of ITRF2008 Argus, 2012;Collilieux et al, 2014], implying we cannot identify which of the underlying geodetic techniques (VLBI/SLR or GPS) is preferred for long-term scale stability. Though we can discern some small interannual variations in the time series, there is no evidence of the abrupt (∼1 ppb) scale instabilities which originally implicated the GPS satellite antenna models as significant error sources [Ge et al, 2005]. While some of the remaining systematic variations could be due to the changing composition of the GPS constellation and ground network, these discrepancies may also stem from the aging of ITRF2008.…”
Section: Results: Scalementioning
confidence: 66%
See 1 more Smart Citation
“…This small relative drift is close to the estimated error of ITRF2008 Argus, 2012;Collilieux et al, 2014], implying we cannot identify which of the underlying geodetic techniques (VLBI/SLR or GPS) is preferred for long-term scale stability. Though we can discern some small interannual variations in the time series, there is no evidence of the abrupt (∼1 ppb) scale instabilities which originally implicated the GPS satellite antenna models as significant error sources [Ge et al, 2005]. While some of the remaining systematic variations could be due to the changing composition of the GPS constellation and ground network, these discrepancies may also stem from the aging of ITRF2008.…”
Section: Results: Scalementioning
confidence: 66%
“…Ge et al [2005] demonstrated that errors in contemporaneous international (IGS) standards for the GPS APC induced a rapid scale change of about 1 ppb over 1 year. They attributed this effect to the evolution of the GPS space segment: as legacy satellites were gradually replenished with modernized systems, the ensemble effect of the APC errors on the different satellite types (blocks) changed.…”
Section: Gps Transmit Antennasmentioning
confidence: 99%
“…As this pattern is visible for all four AC solutions, the network distribution is probably not responsible for this behavior. Ge et al (2005) have already reported such scale changes related to the satellite constellation changes. It might be possible that the IGS calibrated APCOs are not yet optimal but this needs to be demonstrated.…”
Section: Gps Scalementioning
confidence: 93%
“…First, slowly varying systematic errors may map into quasi-secular bias in site positions. One example of this is provided by Ge et al (2005) who demonstrated satellite-specific antenna phase centre offsets from the satellite centre of mass. As the design of in-orbit GPS satellites has evolved over time, neglecting this bias resulted in a quasi-secular variation in GPS scale.…”
Section: Introductionmentioning
confidence: 99%